Double Adenoma as a Cause of Primary Hyperparathyroidism: Asymmetric Hyperplasia or a Distinct Pathologic Entity? - Goodsell, Kristin E. (Am J Surg, 2021)
BACKGROUND: Primary hyperparathyroidism (PHPT) caused by double adenoma may carry a higher risk of failure to cure. We compared outcomes in single adenoma (SA), double adenoma (DA) and four-gland hyperplasia (HP). METHODS: Patients undergoing initial parathyroidectomy for PHPT were categorized by diagnosis. The primary outcome was persistent/recurrent disease postoperatively. RESULTS: Of 3,408 patients, 81.3% had SA, 9.5% had DA, and 9.3% had HP. Rates of persistence/recurrence were 2.9%, 5.3%, and 4.5% in SA, DA, and HP, respectively (p=0.281). Patients with persistence/recurrence had higher preoperative calcium (11.0 vs 10.7 mg/dl, p=0.028) and PTH (96 vs 77 pg/ml, p=0.015), and lower rates of IOPTH normalization (77% vs 96% p<0.001). On multivariable regression, DA was associated with increased risk of persistent/recurrent disease (OR 3.0, p=0.017). CONCLUSIONS: Most patients with DA are cured with removal of two glands, but approximately 5% experience disease persistence/recurrence. Low-normal final IOPTH was associated with lower risk of persistent/recurrent disease.